Screening of antagonistic bacteria for biocontrol activities against Fusarium oxysporum and Ganoderma boninense - Nurul Ashiqin Mat Nawi. (2013)
Ganoderma boninense is a fungus that is pathogenic on oil palms causing basal stem rot and most destructive disease of oil palm in South-East Asia. Meanwhile, Fusarium oxysporum is a causal agent of Fusarium wilt which affects a broad range of plants including black pepper, cucumber, banana and tomato. This study determined the potential of antagonistic bacteria that inhibited againts G.boninense and Foxysporum growth. Five types of bacteria isolates, BLH, B38, B40, B41 and B43 were used for screening of their antagonistic activity againts G.boninense and Foxysporum. The bacteria isolates were screened for in vitro antagonistic activity towards both fungal, G.boninense and Foxysporum through dual culture and culture filtrate test/ diffusible antibiotic. The result showed that all of the bacteria isolates inhibited the growth of Foxysporum and G.boninense with percentage of inhibition radial growth (PIRG) values ranging from 47.57 to 63.78% and 38.8 to 62.0%. Isolates B43 showed highest antagonism against Foxysporum and G.boninense mycelia with 83.19 and 97.37% in culture filtrate test. The antifungal activities apparently involved the secretion diffusible bioactive compounds. Information obtained from this study showde the potential of B43 as biocontrol agent against G. boninense and Foxysporum. It might be an economical as well as environmental save way to suppress the diseases.